Debt overhang paradox and public investment on economic growth in indebted countries : a Southern African - Makgatho, Monica Molefe (My University, 2024)
A multitude of Highly Indebted Poor Countries (HIPC) receive debt relief under the HIPC initiative. As a result, there has been a stimulating debate regarding the effect of elevated levels of external borrowing on economic growth. Over the years, there has been an ever-increasing level of unemployment, price instability, and inequality in the SADC region reflecting rapid declines in economic growth and inefficiency. This study was aimed at investigating the impact of the debt overhang paradox of external debt and debt service cost, and public investment on economic growth in Highly Indebted Countries (HIC) and Less Indebted Countries (LIC) in the SADC region. Panel Vector Error Correction Model (PVECM) and Impulse Response Function (IRF) were employed to determine the short and long-run relationship and to forecast the behaviour of economic growth during the period 2004 to 2020. The PVECM test was conducted which indicated that in HIC debt service cost and public investment have a negative long run relationship with economic growth. The opposite was realised for external debt. In the short run, all the variables were found to have a negative impact on economic growth with the exception of public investment in HICs. The relationship between the explanatory variables and economic growth was found to be statistically insignificant in the short run. Comparably, external debt and public investment in LICs had a positive long run relationship with economic growth, though, a negative relationship was realised between debt service cost and economic growth. The IRF indicated that in HIC, changes in GDP yield either a negative or positive response to past values of GDP. Interestingly, GDP responded positively to debt service cost and public investment while, on the contrary, GDP responded negatively to external debt. Conversely, in LICs, changes in past values of GDP yielded a positive impact on GDP. In contrast, GDP responded negatively to external debt and debt service costs but responded positively to public investment. The results implied that governments in the selected SADC countries spend more than they are able to generate for the average spending needs. Thus, dependency on external borrowing has brought about growth limitations. It is imperative for policymakers to redirect policy to rethink current means of sourcing revenue into more fundamental strategies that enable economic growth and debt repayment simultaneously.
Thesis (M. Com. (Economics)) -- University of Limpopo, 2024
Keywords: External debt; Debt service costs; Public investment; Economic growth; SADC; Debts, External; Capital costs; Economic development; Public investments